The missing link in gravitational-wave astronomy: discoveries waiting in the decihertz range - Arca Sedda, Manuel; Berry, Christopher P. L.; Jani, Karan; Amaro-Seoane, Pau; Auclair, Pierre; Baird, Jonathon; Baker, Tessa; Berti, Emanuele; Breivik, Katelyn; Burrows, Adam; Caprini, Chiara; Chen, Xian; et al. (Classical and quantum gravity, 2020)
The gravitational-wave astronomical revolution began in 2015 with LIGO's observation of the coalescence of two stellar-mass black holes. Over the coming decades, ground-based detectors like laser interferometer gravitational-wave observatory (LIGO), Virgo and KAGRA will extend their reach, discovering thousands of stellar-mass binaries. In the 2030s, the space-basedlaser interferometer space antenna(LISA) will enable gravitational-wave observations of the massive black holes in galactic centres. Between ground-based observatories and LISA lies the unexplored dHz gravitational-wave frequency band. Here, we show the potential of adecihertz observatory(DO) which could cover this band, and complement discoveries made by other gravitational-wave observatories. The dHz range is uniquely suited to observation of intermediate-mass (similar to 10(2)-10(4)M(circle dot)) black holes, which may form the missing link between stellar-mass and massive black holes, offering an opportunity to measure their properties. DOs will be able to detect stellar-mass binaries days to years before they merge and are observed by ground-based detectors, providing early warning of nearby binary neutron star mergers, and enabling measurements of the eccentricity of binary black holes, providing revealing insights into their formation. Observing dHz gravitational-waves also opens the possibility of testing fundamental physics in a new laboratory, permitting unique tests of general relativity (GR) and the standard model of particle physics. Overall, a DO would answer outstanding questions about how black holes form and evolve across cosmic time, open new avenues for multimessenger astronomy, and advance our understanding of gravitation, particle physics and cosmology.
Gesehen am 11.02.2021